A PSYCHOLINGUISTIC STUDY ON COMMUNICATION IMPAIRMENT FOUND IN THE CHARACTER “WHITNEY” IN MAVERICK NOVEL - HARTUTI, SRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Psycholinguistics, Communication Impairment, Speech and Language Impairment, Maverick Novel. People need language to express or deliver messages to others. The process of conveying the messages is called communication. Communication is not successful when people’s speech and language are impaired, which is then called communication impairment. It is a condition when someone cannot use speech and language well. The example of this impairment is depicted in Maverick novel which its main character named Whitney suffers from this impairment. Based on this background, there are 3 problems appear: (1) what are the referral characteristics of speech and language impairment suffered by Whitney?, (2) what are the types of communication impairment suffered by the character“ Whitney” in Maverick novel?, (3) What does the nonverbal communication used by the character “Whitney” in Maverick novel tocommunicate with others?. This study belongs to qualitative research since it focuses on dialogues rather than numbers. In obtaining the data, the writer did some steps: reading the novel, taking notes of the dialogues, and making list. Meanwhile, there are five theories used in this research to answer the problems, they are ADE: Special Education Unit (2014), Lanier (1963), NICHCY (2011), Pearson et al (2006), and DeVito (2005).The result of this study reveals that Whitney suffers from communication impairment. Intellectually, he cannot respond environment with ease. Academically, his writing skill is below expected level. Behaviorally, he prefers to gaze hanging toys than playing with them. Moreover, his communicative ability is weak particularly his speaking ability, and physically, his hearing ability is not very good. In addition, he experiences speech disorder; his articulation is impaired, he repeats the same word many times, and his voice sounds monotonous. Meanwhile, language disorder plays significant role, he cannot follow verbal instruction and even he uses the wrong word in speech. Nevertheless, he still communicates through nonverbal communication by using his body movement: gesture and facial expression. As the conclusion, with these symptoms Whitney suffers from communication impairment.By here, the writer gives suggestions to the readers to be aware of the characteristics of communication impairment and to those who have children to develop their  language ability particularly receptive and expressive. Moreover, it is hoped the next researchers who are willing to conduct in the same field to use this study as the reference. The last, they can find other theories (Morrisey, 2010 or Guralnick, 2002) so that the result can be various.